Psychoanalisis Study of Relationship Between Loyality with Logic Critical Thinking Hermitage of Dimas Kanjeng Followers - Nurul Rodiyah; Aprilia Tri Wahyu Ningrum; Rizki Haidar Aqil; Yayuk Windarti; Novitri Nurimani Asha (e-2477-1929)
The leader of the hermit becomes a figure that attributes the moral guidance of a charismatic society. Charisma owned can lead to assumptions in the community that the leader of the hermitage able to prosper the people. The mindset that considers money as a source of happiness becomes the fostering aspect of deception. Based on the theory of dialectical materialism it can be assured that fraud takes advantage of spiritual morality with the deceitful tricks that lead to blind loyalty and false consciousness. The purpose of this study is to determine the extent of the loyalty of students to Dimas Kanjeng, then in loyalty is how much students use logical critical thinking skills towards  Dimas Kanjeng words. The research method used in this research is interview, participant observation, and documentation study. This research type is mix method, with primary data is purely Dimas Kanjeng’s student, while secondary data obtained from perception of local citizen and radar bromo. The results of the regression analysis show that loyalty has a positive relationship with critical thinking skills, whereas fidelity has a negative relationship with logical thinking.